KINERJA PENGELOLAAN PERSAMPAHAN DI KOTA PEKANBARU - Afriyanni Afriyanni; Kemala Hayati; Nugraheni Restu Kusumaningrum; Khairul Amri (Inovasi Pembangunan : Jurnal Kelitbangan, 2022)
The development of urban areas accompanied by an increase in population has triggered development problems, including the waste problem. This paper aims to describe the performance of solid waste management in Pekanbaru City in terms of 5 (five) aspects, namely: operational technical, institutional, financing, community participation and regulation. This study uses a descriptive qualitative approach with data collection techniques in-depth interviews, documentation studies and observations. Data analysis was carried out by reducing data, analyzing data, presenting data and drawing conclusions. The results of this study found that the performance of solid waste management in Pekanbaru City is still not optimal. Some of the problems faced are: limited Human Resources (HR) and waste infrastructure, low public awareness and participation, weak local regulations enforcement and socialization related to regulations and waste handling mechanisms that are not yet optimal. This study recommends several things, namely: equipping infrastructure and human resources, implementing service transformation, improving Information and Education Communication (IEC), optimizing monitoring and evaluation and enforcement of sanctions, evaluating cooperation with third parties.